Kebijakan Lesspaper dalam Pelayanan Kenaikan Pangkat di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Provinsi Bali - I Gusti Agung Alit Krisnu Saputra (Universitas Warmadewa, 2023)
Lesspaper is a policy in the context of using paper efficiency, this is related to promotion services. Where promotion for state civil servants is a form of agency appreciation for employees for what they have done, or related to achievements achieved by an employee, besides that it can also be a form of giving appreciation to employees for having done their job and responsibilities very well. Through this policy, it is hoped that promotion services will be effective, fast, and not take a long time, which is an advancement in technology related to digitalization. The purpose of this study was to find out how the implementation of the non-paper policy in promotion services at the Bali Provincial Personnel and Resources Development Agency was also to find out what were the inhibiting factors in the implementation policy. The approach in this study uses a qualitative approach that can describe what has been studied. Through data collection by observation, interviews, and documentation. By presenting data in the form of data collection, data reduction, drawing conclusions, and assessing the validity of a data with triangulation techniques. The results of the study show that the implementation of the non-paper policy in promotion services in the Civil Service and Resource Development Section of the Province of Bali has not been carried out optimally, because there is still the implementation of the old policy, namely conventionally. The inhibiting factors consist of communication, human resources and facility resources, as well as dispositions.